2020
DOI: 10.1021/acssynbio.0c00039
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Production of Five Crocins in the Engineered Escherichia coli

Abstract: Crocins are highly valuable medicinal compounds for treating human disorders, and they also serve as spices and coloring agents. However, the supply of crocins from plant extractions is insufficient for current demands, and using synthetic biology to produce crocins remains a big challenge. Here, we report the in vivo production of five types of crocins in E. coli with GjUGT94E13 and GjUGT74F8, which are responsible for the glycosylation of crocetin, from the crocin-producing plant Gardenia jasminoides. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(67 reference statements)
0
14
0
2
Order By: Relevance
“…(electron spray ionization, ESI), 通过对Pittenauer等人 [47] 及Pu等人 [48] 研究中报道的5种西红花苷质谱信息研究 发现, 在正离子模式下5种类型的西红花苷一般不出现 [33,36,37,41,42,49] 以 及毛细管电泳法 [50] 也被用作西红花苷化学结构的表征 研究.…”
Section: 西红花苷质谱学研究主要采用电喷雾离子源质谱unclassified
See 1 more Smart Citation
“…(electron spray ionization, ESI), 通过对Pittenauer等人 [47] 及Pu等人 [48] 研究中报道的5种西红花苷质谱信息研究 发现, 在正离子模式下5种类型的西红花苷一般不出现 [33,36,37,41,42,49] 以 及毛细管电泳法 [50] 也被用作西红花苷化学结构的表征 研究.…”
Section: 西红花苷质谱学研究主要采用电喷雾离子源质谱unclassified
“…天然产物主要源于自然界 的馈赠, 其中不乏具有宝贵药用价值的化合物, 是药物 研发的重要宝库 [84] . 合成生物学的产生及应用能够大大 缓解天然产物价格昂贵、资源匮乏等问题 [48,85] , 如青蒿 酸…”
Section: 糖基转移酶(Ugts)催化西红花酸生成西红 花苷unclassified
“…It has also been reported that crocins show biological functions, such as neuroprotective effects [7], anti-inflammatory activities [8], neurodegenerative diseases [9], allergic airway asthma [10], cardioprotective effects [11], counteracting performance deficits [12], potential therapy for Alzheimer's disease [13], retinal ganglion cell protection [14], platelet apoptosis protection and platelet aggregation inhibition [15], and demyelination and neurodegeneration prevention [16], in animal models. In addition, as kinds of colored apocarotenoids, crocins are often used as valuable spices and colorants in the food industry [17,18]. They originate from the stigmas of Crocus sativus (saffron), which has been reported to be the most expensive spice and colorant in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitation of obtaining this type of compound, the commercial prices of the two major crocins-crocins I and II-are extremely expensive. Though synthetic biology methods [17,19] have been attempted to be used to produce crocins I and II, isolation from plant resources is still the only method for their largescale production. However, except for saffron, only a few distantly related plants, such as Gardenia jasminoides (which grows in many countries) [17], produce crocins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation